The Influence of Dark Chocolate to Reduce Menstrual Pain in Primary Dysmenorhea - Roiela Arfailasufandi; Funsu Andiarna (Journal of Health Science and Prevention, 2018)
Chocolate contains copper which used by the body to synthesize collagen and neurotransmitters called endorphins. Endorphin hormone would be a analgesic and natural sedative so as to reduce the intensity of pain such as menstruation pain. Dark chocolate contains more cocoa, making it the best choice to get the health benefits. The purpose of this study was to investigated the influence of dark chocolate on reducing mentrual pain in primary dysmenorhea. Thestudy used a quasy-experimental research design to approach non-equivalent control group design. The research was conducted in August 2014 until September 2014 at the University of Muhammadiyah Malang. Acted as research sample, 40 students with dismenorhea primary were taken by purposive sampling technique which was divided into treatment group and control group. The independent variable of this study was the provision of dark chocolate and the intensity of menstrual pain on the student with primary dismenorhea became the dependent variable. Data was analyzed by independent t test. The results of the analysis using an independent t test be obtained significant in value (p) less than alpha (0.000<0.05). Dark chocolate influential on decreasing menstrual pain in primary dysmenorhea.